Repeated Interval Loughborough Soccer Passing Tests: An Ecologically Valid Motor Task to Induce Mental Fatigue in Soccer - Bian, Chao; Ali, Ajmol; Nassis, George P.; Li, Yongming (Frontiers in Physiology, 2022)
Most studies investigating mental fatigue (MF) in soccer utilized a computerized Stroop task to induce MF. However, the traditional key-pressing task has been challenged for its lack of ecological validity. The limited relevance to real-life soccer made it difficult to bridge the gap between research and applied setting. Therefore, a novel soccer-specific inducing task is in urgent need. This study compared a novel MF inducing task in soccer with the Stroop task, and investigated the impact of induced MF on cognitive and soccer-specific skill performance. A randomized, counter-balanced crossover design was employed. Fifteen well-trained male soccer players randomly participated in three MF-inducing tasks. Two of them were motor tasks consisting of 10 repeated interval Loughborough Soccer Passing Test (10xLSPT) or LSPT in a clockwise passing order (10xC-LSPT) with each block starting every 2 min. The two tasks share the same movement pattern but C-LSPT is considered to have lower cognitive demands. The third was 20-min Stroop task (Stroop-20). MF was assessed immediately before and after each task by visual analog scale (VAS), the cognitive performance in a 3-min Stroop task and the skill performance in one LSPT. Subjective MF increased similarly after 10xLSPT and Stroop-20 (+25.4±10.3 VS +23.4±10.8 AU, p=0.607). The induced MF by 10xLSPT and Stroop-20 had no impact on cognitive performance and movement time, but similarly affected, in a significantly negative manner, on penalty time (+5.9±4.9 VS +5.4±4.2 s, p=0.748) and passing accuracy (-1.4±1.5 VS -1.0±1.3, p=0.465). Two motor tasks shared similar intensity but 10xC-LSPT was inefficient to induce MF. The results showed that the 20-min repeated interval LSPT could induce a similar MF as Stroop task. The induced MF had detrimental effects on soccer skill performance. The novel motor task is recommended for MF studies in soccer as an inducement task. Practitioners should be cautious about prolonged cognitive demanding skill section of pre-match warm-up to avoid negative effect of MF on upcoming match. This motor task pattern could be followed as a supplementary training protocol.